Cell Signaling Switches HOX-PBX Complexes from Repressors to Activators of Transcription Mediated by Histone Deacetylases and Histone Acetyltransferases - Saleh, Maya (American Society for Microbiology, 2000)
The Hoxb1 autoregulatory element comprises three HOX-PBX binding sites. Despite the presence of HOXB1 and PBX1, this enhancer fails to activate reporter gene expression in retinoic acid-treated P19 cell monolayers. Activation requires cell aggregation in addition to RA. This suggests that HOX-PBX complexes may repress transcription under some conditions. Consistent with this, multimerized HOX-PBX binding sites repress reporter gene expression in HEK293 cells. We provide a mechanistic basis for repressor function by demonstrating that a corepressor complex, including histone deacetylases (HDACs) 1 and 3, mSIN3B, and N-CoR/SMRT, interacts with PBX1A. We map a site of interaction with HDAC1 to the PBX1 N terminus and show that the PBX partner is required for repression by the HOX-PBX complex. Treatment with the deacetylase inhibitor trichostatin A not only relieves repression but also converts the HOX-PBX complex to a net activator of transcription. We show that this activation function is mediated by the recruitment of the coactivator CREB-binding protein by the HOX partner. Interestingly, HOX-PBX complexes are switched from transcriptional repressors to activators in response to protein kinase A signaling or cell aggregation. Together, our results suggest a model whereby the HOX-PBX complex can act as a repressor or activator of transcription via association with corepressors and coactivators. The model implies that cell signaling is a direct determinant of HOX-PBX function in the patterning of the animal embryo.